PLEIOTROPIC EFFECT OF NEBIVOLOL: RECENT DATA - O. Yu. Shaydyuk; E. O. Taratukhin (Российский кардиологический журнал)
The article focuses on the review of recent data on Nebivolol as hypotensive and cardioprotecting medication. The accent is set upon the specific properties of nebivolol, partly, its influence on nitric oxide metabolism. The new information is provided on the study of pleiotropic effects of the drug.